(untitled) (International Journal of Environmental Sciences, 2025)
This study examines the relationship between infrastructure development and economic growth in Pondicherry, India, using Principal Component Analysis (PCA) to analyse key indicators of infrastructure and economic performance. Infrastructure, encompassing transportation, education, health, and agriculture, is crucial for fostering economic development and improving quality of life. The research identifies two primary dimensions of infrastructure development: general infrastructure (roads, educational institutions, banking services) and agricultural-health infrastructure (irrigated areas, public health institutions). These dimensions significantly impact Pondicherry’s economic and rural development. PCA results show that general infrastructure accounts for 42% of the variance, emphasizing the importance of connectivity, education, and financial access. Agricultural and health infrastructure contributes 30% of the variance, highlighting its role in rural livelihoods. On the economic front, the study reveals that economic growth is driven by GDP, literacy rates, and industrial activity, while social challenges like infant mortality and poverty rates require targeted interventions. The findings underscore the need for a balanced approach to infrastructure investment and social policy to achieve sustainable and inclusive development in Pondicherry. By addressing both economic and social dimensions, the study provides insights into policy interventions that can enhance infrastructure effectiveness and promote comprehensive regional development.